(untitled) (Economic and Political Thought, 2012)
The article aims to answer several key questions, namely: What does diversity in higher education concern? What is the relationship between diversity and university rankings – do and what dimensions of higher education diversity create favorite conditions for reaching high positions in rankings? What is the role of competition on the one hand and government policy on the other hand in maintaining or upgrading a position in rankings? What other conditions of the functioning of universities are crucial for diversity and the improvement of productivity and scientific quality? And last but not least, in what conditions do the Polish universities function and what should be done to upgrade their positions in the global rankings and maintain their diversity? The answers to these questions are surprising and have great utilitarian importance.